The trace consistency measurement between WFD-net systems - Zhao, Fang; Xiang, Dongming; Liu, Guanjun (Frontiers in Computer Science, 2023)
How to measure the trace consistency between process models in workflow net systems has become a crucial part of process mapping, process integration, and difference testing. Workflow net with data (WFD-net) is an effective language to describe a complete model of a workflow net system. Checking their trace consistency is a significant challenge in service-based software engineering. However, most of the existing research on trace consistency measurement has not taken the data into consideration. Therefore, they cannot accurately calculate the trace consistency degree of two WFD-net systems, especially when data operations and guard functions are complex. To solve this problem, we explore all traces in two WFD-net systems based on guard analysis and data dependencies. We point out that the trace consistency degree is uncertain when the values of guard functions are considered. Finally, we conduct experiments to evaluate our method and show its effectiveness.